LEARNING OF WRITING POEM USING AUDIO VISUAL ASSISTED IMAGINATION SUGGESTIVE METHOD - Erlin Varlina Rahayu; Ika Mustika (JLER (Journal of Language Education Research), 2020)
Background of the research is based by the difficulties of students in writing poem and learning to be student-centered, at the initial observation of the value of the students are less satisfactory. The purpose of this research is to know the difficulties of learners in writing poem and to understand student value acquisition using a method of audio visual assisted imagination suggestion that seeks to focus on learners. The research method used is a qualitative descriptive approach. The population in this study was 200 class X SMA Negeri 1 Banjaran. Sampling uses rendom sampling, obtained by class X-A as a sample in this study, as many as 32 students. The results earned the highest value students of 92, the lowest value of 67 and an average value of 78.6 with a percentage of 78.6%. A total of twenty-seven students earned their value on the minimal criteria prescribed by the school. The students ' difficulties in writing poem lie in the use of images and Magi. It can be concluded that after a tretment using the method of suggestive imaginary audio visual then the acquisition of grades of students become satisfactory and students are able to overcome the difficulties he faced.